478 The Relationship between Sleep Disordered Breathing, Markers of Ventricular Repolarization and Cardiovascular Mortality. (3rd May 2021) - Patel, Salma; Zareba, Wojciech; LaFleur, Bonnie; Couderc, Jean-Philippe; Xia, Xiaojuan; Woosley, Raymond; Combs, Daniel; Patel, Imran; Mashaqi, Saif; Perez, Karolina; Parthasarathy, Sairam
Abstract: Introduction: Sleep disordered breathing (SDB) is associated with increased mortality. Obstructive apneas/hypopneas have been associated with an increase in both QTc duration and QT variability. These markers of ventricular repolarization are associated with arrhythmias and death. It is unknown whether SDB-related QTc changes are responsible for the relationship between QTc/QT variability and cardiovascular death (CVD). Methods: From the Sleep Heart Health Study, we randomly selected 200 subjects in each of four groups based on overall apnea/hypopnea index: those with no SDB and those in either, mild, moderate or severe SDB at baseline, matched for gender, age and BMI. Respiratory-related channels and electrocardiograms (ECG) from each polysomnography were analyzed. QTc was calculated using Bazett's heart rate correction. The following measures of QT variability were obtained: i) standard deviation of QT intervals (SDQT) at 1- and 5-minute intervals and ii) short-term interval QT variability (STVQT) at 5-minute intervals. Cox proportional hazards regression models were used to evaluate potential predictors of CVD. Results: Twenty-nine subjects were excluded either due to missing data or low quality ECG. The 771 subjects included were 68±10 years of age, half were female. During follow-up, 220 subjects (28.5%) died of CVD among whom, 67 (30.5%) had comorbid severe SDB, 45 (20.5%) had no SDB, and the remaining CVD deaths had mild (47, 21.4%) and moderate 61 (27.7%) SDB. The CVD patients were more likely to be older(p<0.001), hypertensive (p<0.001), diabetic(p<0.001), and had increased SDQT(p<0.001), STVQT(p<0.001) and QTc (0.017). After adjusting for covariates, the presence of mild (p=0.562), moderate(p=0.439) and severe SDB (p=0.912) did not moderate the association between QTc prolongation and CVD. Additionally, mild (p=0.486), moderate(p=0.478) and severe SDB (p=0.849) did not moderate the association between SDQT and CVD. Similarly, mild (p=0.144), moderate(p=0.594) and severe SDB (p=0.508) did not moderate the association between STVQT and CVD. However, QTc, SDQT, STVQT, mild and severe SDB were individually associated with CVD (p=0.004, 0.000, 0.000, 0.014, 0.022, respectively). Conclusion: SDB was not a factor in the relationship between QTc prolongation/QT variability and CVD. Support (if any): American Academy of Sleep Medicine Foundation (203-JF-18), National Institutes of Health (HL126140), University of Arizona Health Sciences Career and Development Award (5299903)